PROBATION SERVICE AS PART OF PENITENTIARY SYSTEM IN THE REPUBLIC OF MACEDONIA - Veljanovska, Svetlana (The European Journal of Applied Economics, 2013)
The reform of the system of execution of sanctions is anticipated in the part of the reform of the criminal justice system of the Republic of Macedonia. The functional system for implementing sanctions in modern criminal justice systems implies a complex approach in which besides the dimension of punishment, the dimensions of social reintegration and victim protection play an important role. In such a context, the so-called probation system, has been established. Event though such system has not been established in the Republic of Macedonia up to now, its elements are contained in the existing legal framework in the material and procedural provisions. Some solutions of the previous system can be used with the aim to establish continuity on institutional and operational level.The starting point for the establishment of probation begins with amendments to the Criminal Code of 2004, where in the part that refers to criminal sanctions, the following alternative measures were imposed: probation, suspended sentence with supervision, conditional discontinuation of criminal proceedings, community service, court sanctions and house arrest. The probation is primarily directed towards designing and developing the system of regular individualized assessment of perpetrators, assessing the risk of re-offending, identifying objective and subjective reasons for previous criminal activity and enabling people who already served their prison sentence to have an active and meaningful involvement in the community.